Sport commitment in young soccer players: A self-determination perspective - Pulido, J. J.; Sánchez-Oliva, D.; Sánchez-Miguel, P. A.; Amado, D.; Garcia-Calvo, T. (International Journal of Sports Science & Coaching, 2018)
Objectives grounded on the self-determination theory, the aim of this study was to assess the impact of perceived need support/thwarting, psychological needs satisfaction/frustration and motivation on young soccer players` sport commitment. Equipment and methods We used a sample of 430 male soccer players (Mage = 14.21 years, SD = 1.67 years, range = 12-18 years). Results Structural equation model analysis ( 2/df = 2.31; CFI = 0.91, TLI = 0.89, GFI = 0.91, SRMR = 0.03, RMSEA = 0.05) showed that coach supporting style positively correlated with players` needs satisfaction, which, in turn positively predicted intrinsic motivation, which, in turn positively predicted sport commitment. On another hand, coach thwarting style positively predicted needs frustration, which positively predicted amotivation, and amotivation negatively predicted sport commitment. Conclusion The coach-created training environment can be crucial for the satisfaction or frustration of the basic psychological needs and, as a consequence, it could play an important role in young soccer players` sport commitment. ABSTRACT FROM AUTHOR